Layanan Rehabilitasi Korban Penyalahgunaan Napza Untuk Wanita di Sentra Insyaf Medan - SSami Hadisti Br Perangin Angin; , Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Rehabilitation services for victims of drug abuse are usually dominated by men, but it is different in the Medan Insyaf Center which has rehabilitation services for women using the Theurapetic Community (TC) program. The number of social welfare service needs (PPKS) for women drug abuse victims at the Insyaf Center in Medan is not much compared to the many issues in society that it is embarrassing for women to be rehabilitated and the community also knows little about the existence of rehabilitation services for women drug abuse victims. a program that is given to women for six months with various activities carried out every day, the Theurapetic Community (TC) program that is used is the same as programs implemented in various rehabilitation services so that the need for social welfare services (PPKS) can change their behavior. The program itself is neatly arranged from getting up in the morning to going to bed at night every day. The many well-organized activities will not make the need for social welfare services (PPKS) for drug abuse victims feel bored or bored during the six-month long program. There are also those who don't want to go home because they need social welfare services (PPKS) to feel comfortable while carrying out the program and feel safe when they are in the Medan Insyaf Sentra environment. So the rehabilitation services for victims of drug abuse are not only for men, but women who are using drugs can also undergo rehabilitation.